Territorial and agonistic interactions between farmed and wild cod (Gadus morhua) - Sverdrup, G; Meager, J J; Ferno, A; Skjaeraasen, J E; Rodewald, P; Salvanes, A G V; Jarvi, T (Aquaculture Research, 2011)
Studies of contest competition between wild and farmed fish have mostly focused on fish with strongly territorial behaviour. Little is known about species with more plastic social behaviour, such as Atlantic cod (Gadus morhua L.), a species that can either aggressively defend territories or shoal. There is also concern that cod that escape from farms will compete with wild populations. We examined dyadic contest competition between wild and farmed juvenile cod using an intruder–resident experimental set-up in the laboratory. No prior residency advantage was observed, but the differences between farmed and wild cod were clear. Farmed cod were more submissive than wild cod and fled earlier during contests, which suggests that wild fish often out-compete farmed intruders. Both fish types initiated aggression earlier against fish of the same background. A multivariate analysis of 11 different behavioural traits indicated that a group of 59% of farmed fish were behaviourally very similar to the 55% most submissive wild fish. These results suggest that wild juvenile cod may be quite robust towards competition for food and shelter from juvenile farmed cod, but further research is needed to verify this pattern.